Performance based budgeting as an instrument of efficient resource alocation at the level of local self-goverment in the Republic of Serbia - Nikodijević Marija (Trendovi u Poslovanju)
Due to the problems with unregulated and unsustainable system of local public finance, local self-governments in the Republic of Serbia are characterized by non-transparent and inefficient use of budget funds which adversely affects the scope and quality of public goods and services. Pointing to the mismanagement of public finances at the local level, as a possible solution to these problems, the paper proposes the implementation of performance-based budgeting. The paper describes the main characteristics of this budgeting model which is an important part of the broader process of public sector reform. The basic principle of performance-based budgeting is reflected in the cause-effect of spent budget funds and the achieved results. In order to make the implementation of this model possible, a series of changes in various spheres should be made, which would provide the necessary preconditions for its implementation. So, the paper points to the key changes that must be implemented and describes the challenges local governments would face when implementing performance based budgeting. In this regard, special attention in the work is paid to the development of an adequate performance measurement system which should enable an evaluation of the effectiveness and efficiency of the public resources spending and should create an accurate and reliable basis for determining the responsibility for achievement (or nonachievement) of results.